Benzoxazole derivatives as phototriggers for the release of butyric acid - Soares, Ana M. S. (2014)
In order to evaluate the application of new benzoxazoles and following the previous work regarding benzoxazoles as photoactive groups and using butyric acid as model, in the preparation of carboxylic acid derivatives, butyric ester conjugates were synthesized by reaction with the chloromethylated heterocyclic precursors.1-3 Photocleavage studies of the ester conjugates in methanol/HEPES buffer (80:20) solution at different wavelengths of irradiation (254, 300, 350 and 419 nm) confirmed the quantitative release of the model acid in short irradiation times.